1974
DOI: 10.1002/hlca.19740570841
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduzierte Cycloadditionen von aliphatischen 2H‐Azirinen. 37. Mitteilung über Photoreaktionen

Abstract: The purely aliphatic 2,3-dipropyl-ZH-azirine (1) reacts on irradiation with a iiiercury high-pressure lamp through a Vycor filter with inethyl trifluoroacetate or acetone to form 3-oxazolincs 3a, b (6.57;) resp. 4 (147;) (Scheme I ) . 9-Azabicyclo[6.1.O]non-l(9)-ene (5) on irradiation in the presence of the dipolarophiles methyl trifluoroacctate, methyl difluoroacetate, 1, 1, 1-trifluoro-propanone and acetone behaves in a similar way, whereby the corresponding bicyclic 3-oxazolines 7-10 result in yields of 60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Weber and co-workers have recently observed the all-carbon analogue of this rearrangement30 and Wendling and Bergman have reported on a closely related thermal rearrangement of a structurally related 1 -phenylazabutadiene.31 The conversion of 28 to 42 is also related to the photocyclization reaction of a number of phenyl unsaturated amides which has been suggested to proceed via a similar pathway.32"34 Involvement of a nitrile ylide intermediate (41) in the rearrangement of 23 to 28 was demonstrated by carrying out the photolysis of 23 in the presence of the very reactive dipolarophile methyl trifluoroacetate. 35 Under these conditions, the formation of 28, which is produced in quantitative yield in the absence of a trapping reagent, is entirely suppressed. The only product isolated was the 3-oxazoline 44.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Weber and co-workers have recently observed the all-carbon analogue of this rearrangement30 and Wendling and Bergman have reported on a closely related thermal rearrangement of a structurally related 1 -phenylazabutadiene.31 The conversion of 28 to 42 is also related to the photocyclization reaction of a number of phenyl unsaturated amides which has been suggested to proceed via a similar pathway.32"34 Involvement of a nitrile ylide intermediate (41) in the rearrangement of 23 to 28 was demonstrated by carrying out the photolysis of 23 in the presence of the very reactive dipolarophile methyl trifluoroacetate. 35 Under these conditions, the formation of 28, which is produced in quantitative yield in the absence of a trapping reagent, is entirely suppressed. The only product isolated was the 3-oxazoline 44.…”
Section: Resultsmentioning
confidence: 98%
“…The resulting organic layer was washed with a 5% sodium bicarbonate solution and was dried over sodium sulfate. Removal of the solvent left 257 mg (74%) of a white solid, mp 23-24 °C, which was assigned the structure of 2-trifluoromethyl-4-trifluoroacetoxymethyl-5-phenyloxazole (32): IR (neat) 5.53 µ; NMR (CDC13, 60 MHz) 4.45 (2 H, s) and 2.63 (5 H, m); UV (95% ethanol) 263 nm (e 14 700); m/e 339 (M+), 243, Chromatography of this material over silica gel resulted in the quantitative formation of 2-trifluoromethyl-4-hydroxymethyl-5phenyloxazole (35).…”
Section: Experimental Section47mentioning
confidence: 96%
See 1 more Smart Citation
“…Some of the dipolarophiles used in-clude azodicarboxylates,30 acid chlorides,31 vinylphosphonium salts,32 and p-quiñones. 33 Photochemical Dimerizations of 2fl-Azirines Irradiation of arylazirines with olefins of low dipolarophilic activity produced no photoadduct but instead gave dimers.18'22'29 Originally it was reported that photolysis of phenylazirine (23) gave azabicyclopentane 24.8'9 However, stimulated by the foregoing mechanistic rationale developed for the photolysis of azirines, we showed that the photodimer isolated is actually diazabicyclohexane (25). Thus, in the absence of an added dipolarophile, the nitrile ylide generated photochemically simply adds to the ground-state azirine molecule.…”
Section: Features Of the Cycloaddition Processmentioning
confidence: 91%
“…Whereas the cycloaddition of arylazirines with simple olefins produces A^pyrrolines, a rearranged isomer can be formed when the alkene and the azirine moieties are suitably arranged in the same molecule. We first observed this intramolecular photocycloaddition using 2-vinyl-substituted azirines.50'51 Irradiation of azirine 32 in benzene afforded a 2,3-disubstituted pyrrole (33), while thermolysis gave a 2,5-disubstituted pyrrole (34).…”
Section: Features Of the Cycloaddition Processmentioning
confidence: 99%